2010
DOI: 10.1523/jneurosci.4882-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

A Network Centered on Ventral Premotor Cortex Exerts Both Facilitatory and Inhibitory Control over Primary Motor Cortex during Action Reprogramming

Abstract: Ventral premotor cortex (PMv) is widely accepted to exert an important influence over primary motor cortex (M1) when hand movements are made. Although study of these interactions has typically focused on their excitatory nature, given its strong connections with both ventral and opercular frontal regions, one feature of PMv's influence over M1 may be inhibitory. Paired-pulse transcranial magnetic stimulation (ppTMS) was used to examine functional interactions between human PMv and M1 during the selection and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
155
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(174 citation statements)
references
References 29 publications
17
155
2
Order By: Relevance
“…However, the IPLs of 6 or 8 ms used in previous ppTMS studies made it unlikely that the effects were mediated by such a route (12,23). To investigate this issue further, the present experiment assessed pre-SMA/M1 and rIFG/M1 interactions using a range of IPLs and looked for correlations between TMS effect sizes and white matter integrity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the IPLs of 6 or 8 ms used in previous ppTMS studies made it unlikely that the effects were mediated by such a route (12,23). To investigate this issue further, the present experiment assessed pre-SMA/M1 and rIFG/M1 interactions using a range of IPLs and looked for correlations between TMS effect sizes and white matter integrity.…”
Section: Discussionmentioning
confidence: 97%
“…The intensity of the preceding conditioning pulse was set at 110% of the resting motor threshold (RMT, defined as the minimum stimulator output required to elicit a 50-μV MEP in 5 of 10 trials) of the left FDI muscle (right M1), and the IPL was 8 ms (23,24). Several studies have used similar interhemispheric TMS coil configuration and conditioning and test pulse intensities, because the size of the head precludes placing two TMS coils over frontal and M1 areas in the same hemisphere in some participants and an interhemispheric configuration produces similar results, albeit with a slightly higher intensity conditioning pulse, to an intrahemispheric configuration (16,23). We hypothesized that the preceding conditioning pulse would change the MEP amplitude elicited by the test pulse, depending on the type of the trial (switch vs. stay trial) and the time after center cue color onset (75, 125, or 175 ms) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This effect depends on cognitive state. When the PMv-M1 pathway is endogenously activated during grasping, an excitatory effect is observed (Davare et al, 2009;Buch et al, 2010). Projections from premotor cortex to M1 are glutamatergic, but while some synapse directly onto corticospinal neurons, many synapse onto GABAergic interneurons within M1 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, neuroimaging and transcranial magnetic stimulation (TMS) studies have shown that mid-dorsolateral and ventrolateral prefrontal areas (Bunge, 2004;Duncan & Owen, 2000) and the presupplementary motor area (pre-SMA; Buch, Mars, Boorman, & Rushworth, 2010) are activated by tasks that require the selection and inhibition of responses. For instance, Verbruggen, Aron, Stevens, and Chambers (2010) demonstrated that TMS of the right inferior frontal gyrus (IFG) impaired performance on both a stop-signal task and a dual task, suggesting that this region supports both response selection and inhibition processes.…”
mentioning
confidence: 99%